Photodynamic therapy for male genital lichen sclerosus with urethral stricture—Case report - Nan Hu; Yongzhen Zou; Xun Deng; Lian Zhang; Zhifang Zhai; Rui Yin (Photodiagnosis and Photodynamic Therapy)
Male genital lichen sclerosus (MGLSc) typically impacts the external genitalia, resulting in balanitis, erectile pain, urination symptoms, and/or urinary retention. Urethral stricture develops in up to 20 % of these patients, which is usually found in the distal part of the urethra but can, in severe instances, impact the entire urethra and cause structural changes. Patients with skin lesions limited to the foreskin and partially extending to the glans can typically be cured by circumcision, but the recurrence rate of stricture is high when the glans or urethra is extensively involved. In the following case report, we describe a 45-year-old man with a history of MGLSc for 3 years and urethral stricture for 2 years, and these conditions remained untreated after circumcision. We emphasize that treatment with 5-aminolevulinic acid-induced photodynamic therapy (ALA-PDT) may further improve outcomes in such severe cases.